MORPHOLOGICAL DATA OF THE ORGANS OF HEMATOPOIESIS AND HEMATOPOIESIS - Mukhiddinova Khurshida Samixovna (Лучшие интеллектуальные исследования, 2024)
Annotation. The basis for maintaining the consistency of quantitative and qualitative composition in each cellular link of the blood system is compliance with the basic law of the kinetics of hematopoiesis: the same number of cells are born and die per unit of time. Hematopoietic stem cells have the ability to simultaneously differentiate into all types of blood cells and proliferate to maintain the constancy of their quantitative composition, since there is no replenishment of this pool from the outside in the postnatal period.